1382 Retrospective Audit to Assess Compliance to National Guidance for The Follow-Up of Acute Uncomplicated Diverticulitis and Adenoma Detection Rate at University Hospital Bristol. (12th October 2021) - Newton, L; Huppler, L; McCabe, T; Gourbault, L; Embury-Young, Y; Handa, I; Muir, D; Sivalingam, N; Archdeacon, J; Chan, J; Macleod-Hall, C; Shabbir, J
Abstract: Aim: Diverticulitis is a common cause for acute surgical admissions. UK guidance recommends uncomplicated diverticulitis is managed with antibiotics, and follow-up outpatient lower gastrointestinal (LGI) endoscopy (flexible sigmoidoscopy or colonoscopy) arranged 6-8 weeks after discharge. This audit aimed to assess compliance to national guidance and assess adenoma detection rate. Method: Retrospective analysis of discharge summaries coded 'diverticulitis' from January 2017 – April 2020 at University Hospital Bristol(UHB). Results: 426 patients presented with uncomplicated diverticulitis, mean age 60.5 years (22-92 years). 42% (179/426) of patients underwent LGI endoscopy as an inpatient or on discharge. Median time to outpatient endoscopy was 70 days (6-287 days). 23% (99/426) had LGI endoscopy within the 8-week target. Histology showed: 21% (37/179) polyp; 5% (9/179) tubular adenoma; and one patient had high grade dysplasia. The histology for the remaining 28 patients with polyps showed: hyperplasia; granulation tissue; inflammation; or samples were not sent for histology. No cases of malignancy were detected. Conclusions: 58% of patients admitted with acute uncomplicated diverticulitis did not have a follow-up LGI endoscopy and only 23% had LGI endoscopy within the 8-week target. 21% had a polyp with a 5% rate of tubular adenoma and no cases of malignancy. UHB needs to improve compliance with national guidance for the arrangement of follow-up LGI endoscopy, however the absence of detection of malignancy raises the question of whether we need to re-consider its necessity for patients with uncomplicated diverticulitis.